Os desafios da inovação no ensino médio: uma análise exploratória sobre práticas possíveis - Augusto, Luís Paulo Fagiolo (Universidade Federal de São Carlos, 2021)
In recent years, the practice of innovation has been pointed out as a competitive differential in all sectors of the economy, especially those related to technology. In face of this scenario, the research question that guided the development of this work was: How has innovation been considered in the teaching-learning processes of High School in Brazil? To that end, the specific objectives of the research were: To describe the historical trajectory of education in Brazil, pointing out some historical limitations for the construction of its autonomy, since the colonial period; Partially contextualize, in the field of Science, Technology and Society, the cultural and social implications in education; Raise and examine laws and decrees that influence the teaching of innovation in education; Discuss how the relationship between innovation and education in Brazil took place; Raise and examine national projects and initiatives aimed at secondary education that contribute to the construction of teaching innovation. This research used an exploratory methodology, based on a bibliographic and documental analysis aiming at the search for knowledge and information aimed at understanding the factors of innovation in relation to the conducts used in education. It was concluded that it is complex to establish a standard on the best way to apply innovation in education, and more, what works for a certain country may not work for another, however, there is a common agreement on the need for change. It is premature to affirm that teaching innovation in education is a differential for the country's economic and social progress, however, we must pay attention to this reality.
The challenges of innovation in high school: an exploratory analysis of possible practices
Keywords: Inovação; Educação; Ensino Médio; Innovation; Education; High School; CIENCIAS SOCIAIS APLICADAS